CREATION OF GLOBAL WARMING E-LKPD BASED ON PBL MODEL TO FACILITATE HIGH SCHOOL STUDENTS' SCIENCE LITERACY: NEED ANALYSIS - Tanjung, Sastika; Emiliannur, Emiliannur (PILLAR OF PHYSICS EDUCATION, 2024)
The world of education has undergone major changes due to the rapid development of technology, thus providing challenges to education. To improve education today, the world of education must make the latest innovations..To keep up with the rapid development of the 21st century with the development of technology and knowledge, the generation that is able to keep up must have skills. One of the skills that students must have to improve their knowledge and compete in the field is scientific literacy.. One of the learning resources that can support the learning process is by using electronic teaching materials. Electronic teaching materials that can be used are in the form of E-LKPD. This study uses a qualitative research method. The model used in this study is the ADDIE model. The population in this study were 112 students of class X Phase E in the 2023/2024 academic year. The sample of this study was carried out by random sampling with 30 students as research subjects and 5 lecturers of FMIPA UNP physics lecturers. Based on observations made at SMAN 1 Ulakan Tapakis, there were problems that occurred. The solution that can be done is to create electronic teaching materials in the form of E-LKPD. Based on the problems found, the researcher will create a product in the form of E-LKPD based on the PBL model using liveworksheet.